FORMULASI DAN UJI KELAYAKAN SEDIAAN KRIM ANTI INFLAMASI GETAH TANAMAN PATAH TULANG (Euphorbia tirucalli L) - Agral, Omega; Fatimawali, Fatimawali; Yamlean, Paulina V.Y; Supriati, Hamidah Sri (UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACTHas been formulated the latex of pencil tree plant (Euphorbia tirucalli L) to be a cream.Pencil tree plant latex cream formulated with various concentrations of the active substancesi.e 5%, 10%, and 15%. The formulation of pencil tree plant latex cream produced the cramwith good parameter values.Key words : Cream, Pencil Tree Plant (Euphorbia tirucalli L)